1973
DOI: 10.1071/ch9732533
|View full text |Cite
|
Sign up to set email alerts
|

Metal ion and ligand dependency of the redox behaviour of some first row transition metal dithiocarbamates

Abstract: The one-electron oxidation and reduction processes for some 80 dithiocarbamates of Cr, Mn, Fe, Co, Ni, and Cu reveal a marked dependence of redox potential on the metal 3dn electron configuration. For all the complexes examined, the relative ordering of the redox potentials with the dithiocarbamate substituents is remarkably consistent for both oxidation and reduction processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…The authors of [6], by analogy with gold complexes [AuX 2 ] -(where X is Cl -, Br -, and CN -) assumed that a complex [AuRCA 2 ]X should be formed in the Au-TCA system. However, according to [10][11][12][13][14], the elements of the Ib subgroup of the Mendeleev Periodic System, viz., Cu(I), Cu(II), Ag(I), and Au(I) form thiocarbamide complexes of a [MeTCA n ] + composition (where n = 1, 2, 3, 4). According to [14], depending on the experimental conditions of the anodic dissolution of Ib-subgroup metals, the reaction order in TCA can equal 1, 2, and 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors of [6], by analogy with gold complexes [AuX 2 ] -(where X is Cl -, Br -, and CN -) assumed that a complex [AuRCA 2 ]X should be formed in the Au-TCA system. However, according to [10][11][12][13][14], the elements of the Ib subgroup of the Mendeleev Periodic System, viz., Cu(I), Cu(II), Ag(I), and Au(I) form thiocarbamide complexes of a [MeTCA n ] + composition (where n = 1, 2, 3, 4). According to [14], depending on the experimental conditions of the anodic dissolution of Ib-subgroup metals, the reaction order in TCA can equal 1, 2, and 3.…”
Section: Resultsmentioning
confidence: 99%
“…However, according to [10][11][12][13][14], the elements of the Ib subgroup of the Mendeleev Periodic System, viz., Cu(I), Cu(II), Ag(I), and Au(I) form thiocarbamide complexes of a [MeTCA n ] + composition (where n = 1, 2, 3, 4). According to [14], depending on the experimental conditions of the anodic dissolution of Ib-subgroup metals, the reaction order in TCA can equal 1, 2, and 3. From our viewpoint, such reaction orders of gold electrodissolution in TCA are explained by limited dissolution of gold thiocarbamide complexes ([AuTCA] + ) in aqueous solutions at low ligand (TCA) concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in recent years, there has developed a considerable amount of interest in the reversible redox reactions of these types of metal complexes in solution. 6 It has been shown that oxidation potentials display a marked dependence on the 3d" configurations of the first transition series central metal atoms which supports the conclusion that the redox orbitals of these metal chelates exhibit predominantly metal character. 6 There are numerous reports in the literature of gas phase electron detachment reactions and associated positive ion mass spectra of metal dithiocarbaHowever, few attempts have been made to examine and rationalize the reactions of such compounds with low energy or thermalized electrons in the gas phase,I2 apart from a preliminary investigation which used electron impact (EI) conditions and involved several nickel(I1) dithiocarbamato c~mplexes.…”
Section: Introductionmentioning
confidence: 83%
“…6 It has been shown that oxidation potentials display a marked dependence on the 3d" configurations of the first transition series central metal atoms which supports the conclusion that the redox orbitals of these metal chelates exhibit predominantly metal character. 6 There are numerous reports in the literature of gas phase electron detachment reactions and associated positive ion mass spectra of metal dithiocarbaHowever, few attempts have been made to examine and rationalize the reactions of such compounds with low energy or thermalized electrons in the gas phase,I2 apart from a preliminary investigation which used electron impact (EI) conditions and involved several nickel(I1) dithiocarbamato c~mplexes. '~ Gas phase electron attachment reactions of a series of dithioacetylacetonato complexes of nickel(II), which involve ligands with the odd a-system S2 donor atom set, also have been studied, but the thermal lability of many metal complexes of such ligands precluded the extension of that work to encompass a wider range of metal^.…”
Section: Introductionmentioning
confidence: 83%